PKM Kelompok Guru- Guru TK Rambutan Tentang Pengenalan Aplikasi Canva untuk Pembuatan Video Pembelajarn Interaktif - Agus Darmawan; Syamsiah Syamsiah; Nunu Kustian; Siti Juleha; Irnawati Irnawati (STIKes Ibnu Sina Ajibarang, 2024)
In the ever-growing digital era, education plays an important role in utilizing technology to improve the quality of learning. Interactive learning videos have become an effective tool in delivering learning material in an interesting and competitive way. However, many kindergarten teachers still face challenges in producing interesting and interactive learning videos due to limited knowledge and skills in using appropriate software. TK Rambutan, teachers realize the importance of updating their skills in integrating technology in the learning process. In this context, the introduction of the Canva application as a tool for creating interactive learning videos is considered a progressive step that can help teachers create more interesting and relevant learning experiences for young children. Using Canva as an intuitive creative platform and the various features it offers, such as templates, graphics and animations, can help TK Rambutan teachers in creating learning video content that is interesting, easy to understand and interactive. Therefore, through this Community Service (PKM), TK Rambutan teachers aim to explore the potential of Canva in the context of early childhood education and improve their skills in utilizing this application to create a more interesting and effective learning experience for students.